A Controlled, Randomized-Blinded Clinical Trial to Assess the Efficacy of a Nitric Oxide Releasing Patch in the Treatment of Cutaneous Leishmaniasis by Leishmania (V.) panamensis (2010)
ABSTRACT: A topical nanofiber nitric oxide (NO) releasing patch (≈3.5 μmol NO/cm2/day for 20 days, NOP) was compared with intramuscular meglumine antimoniate (Glucantime, 20 mg/kg/day for 20 days) for the treatment of cutaneous leishmaniasis (CL) caused by Leishmania (V.) panamensis in Santander and Tolima, Colombia. A double-blind, randomized, placebo-controlled, clinical trial was conducted to determine whether the NOP is as effective as Glucantime for the treatment of CL. Patients were randomly assigned to Glucantime and placebo patches or NOP and placebo of Glucantime. The cure rates after a 3-month follow-up were 94.8% for the group that received Glucantime compared with 37.1% in the NOP group. Despite the lower efficacy of the NOP versus Glucantime, a significantly lower frequency of non-serious adverse events and a reduced variation in serum markers were observed in patients treated with NOP. Treatment of CL with NOP resulted in a lower effectiveness compared with Glucantime; however, the low frequency of adverse events and the facility of topic administration justify the development of new generations of NOP systems for the treatment of CL